Unravelling the persistence of dollarization : the case of Georgia - Eradze, Ia (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This volume engages with the roots, dimensions and implications of foreign currency domination in states with a national currency. Referred to as unofficial dollarization in literature, this is a worldwide phenomenon among developing countries and has a long history. This monograph provides a political economic analysis of dollarization in Georgia and is structured around three themes: the genesis of dollarization (1991-2003), the persistence of dollarization (2003-12) and the politicization of dollarization (2012-19). The case of Georgia is especially representative of the post-socialist transition states, but also has wider applicability. A high level of dollarization is a significant barrier to economic growth, macroeconomic and political stability, functional monetary policy, as well as social welfare. The Covid-19 crisis and the increasing debt of developing countries in foreign currency exacerbate dollarization-related vulnerabilities for these economies. This book will be of interest to postgraduate students in global/comparative political economy, development economics or transition economies, researchers in monetary sovereignty, central banking, exchange rate policies, currency hierarchy, money, financialization, and policy makers in dollarized countries and global institutions"--
Keywords: Dollarization -- Georgia (Republic); Monetary policy -- Georgia (Republic); BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Economic Conditions; BUSINESS & ECONOMICS / Development / Economic Development